Peningkatan Kemampuan Membaca Pemahaman Melalui Strategi Directed Reading Thinking Activity (DRTA) Berbantuan Media Storybook Gemini AI Pada Siswa Kelas V di SDN 32 Bungo Pasang - Ikhsan Nurhakim, Satrio; Suriani, Ari; Kharisma, Inggria; Sukma, Elfia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low achievement in students' reading comprehension scores in the Indonesian language subject at SDN 32 Bungo Pasang forms the background of this research. Student scores indicating the non-achievement of KKTP serve as a symptom of this problem. Students face difficulties in understanding texts and tend to be passive during the learning process, making them less capable of grasping, summarizing, and answering questions about reading materials. Furthermore, the classroom learning does not utilize a deep learning approach. The Directed Reading Thinking Activity (DRTA) strategy assisted by Gemini AI Storybook is employed to overcome these learning issues. The objective of this study is to delineate how students' reading comprehension skills enhance within Indonesian language instruction. To evaluate its efficacy, this classroom action research implemented a combination of qualitative and quantitative methodologies. The research instruments used were RPPM observation sheets, teacher and student activity sheets, and assessment rubrics for attitude, knowledge, and reading comprehension skills. The study was conducted through the stages of planning, acting, observing, and reflecting across two cycles. Cycle I consisted of two meetings, followed by cycle II with two meetings, involving 27 fifth-grade students as subjects. The results demonstrated improvements across all aspects. The RPPM in cycle I obtained 93.75%, increasing to 100% in cycle II; teacher activity in cycle I achieved 84.14%, increasing to 100% in cycle II; student activity in cycle I averaged 82.14%, increasing to 92.86% in cycle II. Student learning outcomes also improved, where the average of 66.36 obtained in cycle I increased to 78.52, and finally rose to 87.64 in cycle II.